Thermomechanical evaluation of geopolymeric and conventional concretes - Huamán-Mamani F.A. (2020)
Geopolymers are a class of inorganic synthetic materials that in recent years have received extensive interest of the scientific community, mainly due to the variety of applications in which they can be used. The synthesis of these materials is based on a chemical process called geopolymerization, which consists of the alkaline activation of amorphous alumina and silica oxides present in many natural raw materials and industrial solid waste. Therefore, the present work proposes the use of inorganic mining residues (mine tailings) from gold mining in the southern region of Peru, for the manufacture of geopolymeric concrete. The first part of the research focused on the physical, structural and microstructural characterization of the raw material (fine sand and mining tailings), then the volumetric matrix of mixtures for five types of geopolymer concrete was determined. Cylindrical samples of 20 mm diameter and 40 mm high geopolymeric concrete were manufactured, at the same time conventional Portland cement concrete was manufactured for comparison purposes. All materials were mechanically characterized by uniaxial compression tests at variable temperatures (from room temperature to 600 ºC), and they were also microstructurally characterized before and after mechanical tests. The main microstructural mechanisms responsible for the fracture and plastic deformation of geopolymeric and conventional Portland cement concretes have been determined. © 2020, Avestia Publishing. All rights reserved.